Growth in the age of complexity : steering your company to innovation, productivity, and profits in the new era of competition - Perumal, Andrei; Wilson, Stephen A. (Stephen Anthony), 1969- (McGraw Hill Education, 2018)
Providing a new lens on growth and a critical set of strategies for navigating a complex world, this book is an invaluable tool for achieving growth and maintaining a competitive advantage in virtually any business. --